A Novel Method to Image Macropinocytosis in Vivo - Chen, Lunhao; Cheng, Daxiao; Chu, Jiachen; Zhang, Ting; Dong, Zhuoer; Lou, Huifang; Zhu, Liya; Liu, Yijun (Frontiers in Neuroscience, 2018)
Here we described an experimental protocol for in vivo imaging of macropinocytosis and subsequent intracellular events. By microinjection, we delivered fluorescence dextrans together with or without ATPS into transparent Drosophila melanogaster embryos. Using a confocal microscope for live imaging, we monitored the generation of dextran-positive macropinosomes and subsequent intracellular events. Our protocol provides a continent and reliable way for investigating macropinocytosis and its underlying mechanisms, especially when combined with genetic strategies.